Comparative Physicochemical Characterization of Porcine, Fish, and Bovine Gelatin in Gummy Candies: Toward Halal Nutraceutical Development - Laksitorini, Marlyn Dian; Darsih, Cici; Yuniarti, Nunung; Rumiyati, Rumiyati; Abidin, Mohammad Zainal (Pharmaceutical Sciences and Research, 2026)
Gummy candies have emerged as one of the most popular dosage forms for multivitamins and nutraceutical supplements, including those for brain health. Gelatin is the primary gelling agent used to achieve the gummy texture; however, the influence of different gelatin sources on the physicochemical properties of gummies has not been systematically examined. This study investigated the physicochemical characteristics of gummies prepared with porcine, bovine, and fish gelatin. The gummies were evaluated for mechanical properties (gumminess, hardness, cohesiveness, springiness, adhesiveness, and stringiness), color, water activity, antioxidant activity, and protein content. Additionally, the effects of intentional adulteration—specifically the addition of porcine gelatin to fish or bovine gelatin—were assessed. The results showed that gumminess, hardness, cohesiveness, and springiness were comparable across different gelatin sources, whereas adhesiveness and stringiness were highly sensitive to source variation. Notably, adulteration with porcine gelatin significantly altered those two parameters. These findings underscored the importance of verifying gelatin origin in gummy formulations, as source-related variations and gelatin adulteration could have a direct impact on product quality and performance.